The Effect of ESG and Earnings Quality on the Value Relevance of Earnings and Book Value - Aulia Fuad Rahman; Nugroho Suryo Bintoro; Ayu Aryista Dewi; Kholilah Kholilah (Australasian Accounting, Business and Finance Journal, 2024)
This paper aims to investigate the value relevance of ESG (environmental, social and governance) and earnings quality of companies listed on the Indonesia Stock Exchange during the period from 2012 to 2022. Furthermore, this study also investigates the value relevance of earnings and book value in the presence of ESG and earnings quality. The value relevance was operationalized using Ohlson's price model (1995), and data was extracted from the Refinitiv database. Based on 353 firm-years, the panel data analysis indicates that ESG and earnings quality have value relevance; this proves that information about ESG and earnings quality are used by investors and stakeholders as a basis for decision-making. Moreover, the presence of ESG has a negative impact on the value relevance of earnings but has a positive impact on the value relevance of book value. By contrast, with ESG, the presence of earnings quality has a positive impact on the value relevance of earnings but has a negative impact on the value relevance of book value, implying that when the quality of accounting information increases, users rely more on earnings information rather than book value. A robustness test testing was also carried out by conducting sub-sample tests based on the period during which the COVID-19 pandemic occurred during the research. Results show that before the pandemic, users tended to be more interested in ESG information, while during the pandemic, users tended to focus more on earnings quality information as a basis for decision-making.
Keywords: environmental; social; governance; earnings quality; value relevance